Women’s Mourning for the Dead: Between Sharia Rulings and Contractual Violations: A Study in the Light of the Prophetic Guidance - Alenezi, Aied Obied; Abdelrahman, Maria Bassam (Dirasat: Shari’a and Law Sciences, 2023)
Objectives: Some women commit legal and doctrinal violations during mourning, which threatens the doctrinal security of the family. Therefore, this research aims to clarify the manifestations of these violations and demonstrate the Sharia ruling on them. Methods: The study adopted the analytical inductive method. This was done by extrapolating and analyzing texts related to the subject, with the help of modern commentary books. In addition, contemporary phenomena that reflect doctrinal violations related to mourning were analyzed and compared to the Quran and the Sunnah. Results: The study revealed manifestations of doctrinal and Sharia violations in women’s mourning, including imposing mourning on someone other than the husband, non-compliance with the legal period, belief in specifying the color of the mourning dress, refraining from ablution, performing actions that contradict dignity, and expressing discontent with fate by wailing, among others. The study also showed Sharia’s opinion regarding these violations, clarifying the provisions of legitimate mourning, prohibiting such violations, and asserting that they are from the heresies of the jahiliyyah (i.e., pre-Islamic period). Conclusions: The study revealed the violations committed in women’s mourning and demonstrated the Sharia ruling regarding them to protect the family’s doctrinal security. The study recommends the need to intensify efforts to raise awareness of this aspect in family and educational institutions.